Library assistance to readers - Collison, Robert Lewis (London: C. Lockwood, 1960)
The author deals with the technique of assistance in a systematic and comprehensive manner. Assistance to readers is at the heart of librarianship.
obn 22/01/2019
Loans
Keywords: Public services (Libraries); Librarianship